Process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate

By optimizing the ore dressing and smelting process of titanium concentrate, combining sodium chloride quenching and rotary kiln roasting treatment, and finally using hydrochloric acid leaching to remove impurities, the problems of long process, low conversion rate and environmental pollution in the existing process are solved, and high titanium recovery rate and low cost preparation of titanium-rich materials are achieved.

CN119663011APending Publication Date: 2025-03-21中信钛业股份有限公司 +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411851654.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing titanium concentrate preparation titanium-rich material process has problems such as long process flow, low conversion rate, large loss in recycling titanium and serious environmental pollution.

Method used

Selected titanium concentrates with CaO<0.8 wt.%, MgO≤1.5 wt.%, SiO2≤1.2 wt.%, were obtained by ore dressing, and the titanium-rich material was obtained by electric furnace smelting. Sodium chloride was added and quenched. Then, oxidation and roasting were used in a rotary kiln. Finally, impurities were removed by hydrochloric acid leaching to obtain titanium-rich material for boiling chlorination.

Benefits of technology

It has achieved shortening of the production process, improved the titanium recovery rate, reduced the cost of decomposition, and reduced environmental pollution, and obtained high-quality titanium-rich materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663011A_ABST
    Figure CN119663011A_ABST
Patent Text Reader

Abstract

A process for preparing a titanium-rich material from titanium concentrate with a high titanium recovery rate comprises the following steps: carrying out mineral separation on the titanium concentrate to obtain CaOlt; the concentration titanium concentrate comprises 0.8 wt.% of MgO < = 1.5 wt.% and SiO2 < = 1.2 wt.%; smelting the selected titanium concentrate by adopting an electric furnace to obtain molten high-titanium slag, adding sodium chloride accounting for 0.5%-10% of the mass of the molten high-titanium slag into the molten high-titanium slag, stirring, and carrying out quenching treatment to obtain quenched titanium slag; the quenched titanium slag is subjected to oxidizing roasting through a rotary kiln, the roasting temperature of the rotary kiln is 900-1000 DEG C, the roasting time is 10-30 min, and roasted titanium slag is obtained; and the roasted titanium slag is subjected to first-stage hydrochloric acid leaching to remove impurities, the leaching temperature is 140-150 DEG C, the leaching time is 2 hours, and the titanium-rich material for fluidizing chlorination is obtained. The method has the advantages of short production flow, improvement of titanium recovery rate, reduction of impurity removal cost and reduction of environmental pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ilmenite utilization, and particularly relates to a process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate. Background Art

[0002] Titanium dioxide, chemically known as titanium dioxide (TiO2), is a white pigment that is widely used in coatings, plastics, papermaking, inks, rubber, cosmetics and other fields for its excellent whiteness, tinting power and weather resistance. There are two main production processes for titanium dioxide: sulfuric acid process and chlorination process. The chlorination process occupies a dominant position with a market share of more than 60%. The sulfuric acid process has a lower cost, but may produce more by-products and waste. The product of the chlorination process has high purity and stable quality, but it has high requirements for raw materials and relatively high costs. The boiling chlorination process in the chlorination process has strict requirements on the TiO2 content of the raw materials, which must exceed 85wt.%. At the same time, there are also restrictions on the content of CaO and MgO, which should not exceed 0.35wt.% and 1.0wt.%, respectively, to ensure the smooth production process and the stability of product quality.

[0003] China's ilmenite resources generally have high calcium and magnesium contents. The titanium slag obtained after electric furnace smelting is difficult to be directly used in the boiling chlorination process due to the high calcium and magnesium content. At present, the research on the impurity removal technology of titanium slag mainly focuses on the way of chemical leaching to convert the impurity elements into a new phase that is easy to dissolve or acid-leach, and then separate the impurities through the leaching process. CN 113862494A discloses a "method for preparing titanium-rich material and titanium tetrachloride", which comprises: molten high-titanium slag obtained by mixing and smelting titanium concentrate and a reducing agent, water quenching the molten high-titanium slag, acid leaching the obtained water-quenched slag once, and then solid-liquid separation to obtain acid-leached titanium slag; oxidative roasting and reduction roasting are carried out on the acid-leached titanium slag in sequence to obtain a roasted material, and the roasted material is acid-leached twice, and then solid-liquid separation is carried out to obtain a titanium-rich material. Although this method can convert impurities such as calcium and aluminum into acid-soluble Ca3Al2O6 by water quenching, and then remove impurities through acid leaching, oxidation and reduction roasting, and acid leaching again, it can obtain high-quality titanium-rich materials with CaO of 0.15wt.% and CaO+MgO less than 1.5wt.%. However, in the process of preparing boiling chlorination furnace materials from titanium concentrate, this method requires oxidation roasting first, then reduction roasting, and acid leaching before and after roasting. The process is long, the conversion rate is low, the loss of recovered titanium is large, and a large amount of acid leaching waste acid is generated. The process is complicated and polluting. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate, which has a short production process, improves titanium recovery rate, reduces impurity removal cost, and reduces environmental pollution.

[0005] The present invention provides the following technical solutions: A process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate, the specific steps of which are as follows: (1) beneficiating the titanium concentrate to obtain a concentrated titanium concentrate with CaO < 0.8 wt.%, MgO ≤ 1.5 wt.%, and SiO2 ≤ 1.2 wt.%; (2) Smelting the selected titanium concentrate in an electric furnace to obtain molten high-titanium slag, adding 0.5%-10% of sodium chloride by weight of the molten high-titanium slag to the molten high-titanium slag, stirring, and quenching to obtain quenched titanium slag; oxidatively roasting the quenched titanium slag in a rotary kiln, the rotary kiln roasting temperature is 900-1000° C., the roasting time is 10-30 min, and roasted titanium slag is obtained; (3) The roasted titanium slag is subjected to a hydrochloric acid leaching to remove impurities at a temperature of 140-150° C. for 2 hours to obtain a titanium-rich material for boiling chlorination.

[0006] Furthermore, in step (1), the TiO2 content in the raw titanium concentrate is ≥44wt.%, and the ball grinding fineness of the titanium concentrate is -200 mesh ≥90%.

[0007] Furthermore, during ore dressing, the titanium concentrate is first ball-milled, and then sodium oleate and an inhibitor are added, wherein the amount of sodium oleate added is 1500-2000 g / t, and the amount of the inhibitor water glass is 300-800 g / t. The pH value is adjusted to 3-4 with an inorganic acid, and a primary flotation is used for pre-removal of impurities to obtain a selected titanium concentrate.

[0008] Furthermore, the inhibitor is water glass or sodium hexametaphosphate.

[0009] Furthermore, the inorganic acid is a sulfuric acid solution.

[0010] Furthermore, the TiO2 content in the molten high-titanium slag is ≥80wt.%.

[0011] Furthermore, the concentration of hydrochloric acid is 20wt.%.

[0012] Furthermore, after smelting in the electric furnace, when the temperature of the molten high-titanium slag drops to >1600°C, sodium chloride is added and stirred for 5 minutes.

[0013] Furthermore, the calcining atmosphere is a mixed gas of air and oxygen or air.

[0014] Furthermore, in the titanium-rich material used for boiling chlorination in step (3), TiO2≥85wt.%, CaO≤0.2wt.%, MgO≤1.0wt.%, and SiO2≤2.5wt.%.

[0015] The beneficial effects of the present invention are: 1) The present invention optimizes the raw material pretreatment, adopts low-cost flotation impurity removal to pre-select and remove part of calcium and magnesium impurities, and the obtained selected titanium concentrate is subjected to electric furnace smelting to obtain high-quality molten high-titanium slag. The molten high-titanium slag is treated with sodium chloride to assist in quenching, which can destroy the black titanium stone and silicate crystal structure of the titanium slag, and significantly reduce the difficulty of subsequent calcium and magnesium impurity removal. The high-titanium slag is oxidatively roasted in a rotary kiln to achieve rapid transformation of the titanium slag. The leaching process of the transformed titanium slag is short, which reduces the impurity removal cost and environmental pollution, and at the same time reduces the loss of titanium in subsequent acid leaching, so as to achieve low-cost and high-yield preparation of boiling chlorination furnace charge with high calcium and magnesium titanium slag.

[0016] 2) The present invention is based on the whole process from ilmenite beneficiation to boiling chlorination furnace charge preparation. Through beneficiation and impurity removal, the subsequent acid leaching impurity removal load is reduced. After the molten high-titanium slag smelted in an electric furnace is treated with sodium chloride and then quenched with water, the particle structure in the titanium slag is destroyed, and the sodium ions enter the silicate phase, which is beneficial to the subsequent acid leaching impurity removal; the heat of the electric furnace flue gas is used to add part of the air or oxygen to promote the oxidation transformation of the water-quenched titanium slag, which can improve the recovery rate of titanium in the subsequent acid leaching process, and overall realize the low-cost and high-yield preparation of boiling chlorination furnace charge with high calcium magnesium titanium concentrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a process flow chart of Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are further described below by way of examples, but the specific embodiments of the present invention are not limited to the following examples.

[0019] Example 1 (1) A titanium concentrate having a TiO2 content of 45.21 wt.%, a CaO content of 2.75 wt.%, a MgO content of 1.86 wt.%, and a SiO2 content of 3.56 wt.% is ball-milled to -200 mesh ≥ 90%, and pre-impurities are removed by a primary flotation process. During the pre-impurities removal, 2000 g of sodium oleate as a collector and 300 g of water glass as an inhibitor are added per ton of the titanium concentrate, and the pH value is adjusted to 4 with sulfuric acid. The pre-impurities are removed to obtain a selected titanium concentrate having a TiO2 content of 47.15 wt.%, a CaO content of 0.61 wt.%, a MgO content of 0.98 wt.%, and a SiO2 content of 1.12 wt.%, and the yield of the selected titanium concentrate is 94.18%; (2) The selected titanium concentrate is smelted in an electric furnace to obtain a molten high-titanium slag containing 80.68 wt.% of TiO2, 1.23 wt.% of CaO, 1.95 wt.% of MgO and 2.42 wt.% of SiO2, and 5 wt.% of sodium chloride is added to the molten high-titanium slag (the temperature of the molten slag is greater than 1600° C.), and the mixture is stirred for 5 minutes and then quenched to obtain quenched titanium slag; the quenched titanium slag is oxidatively roasted in a rotary kiln at a roasting temperature of 900° C. for 30 minutes in an air atmosphere to obtain roasted titanium slag; (3) The transformed roasted titanium slag is subjected to a one-stage hydrochloric acid leaching process to remove impurities. The hydrochloric acid concentration is 20wt.%, the leaching temperature is 140°C, and the leaching time is 2 hours. The obtained titanium-rich material has a TiO2 content of 88.56wt.%, a CaO content of 0.16wt.%, a MgO content of 0.88wt.%, and a SiO2 content of 2.36wt.%, which meets the boiling chlorination requirements. The titanium recovery rate is 99.12%.

[0020] Example 2 (1) A titanium concentrate having a TiO2 content of 44.69 wt.%, a CaO content of 2.45 wt.%, a MgO content of 1.62 wt.%, and a SiO2 content of 3.89 wt.% is ball-milled to -200 mesh ≥ 90%, and a primary flotation process is used for pre-impurity removal. During the pre-impurity removal, 1500 g of sodium oleate as a collector and 800 g of sodium hexametaphosphate as an inhibitor are added per ton of the titanium concentrate, and sulfuric acid is used to adjust the pH value to 3, thereby obtaining a selected titanium concentrate having a TiO2 content of 47.02 wt.%, a CaO content of 0.70 wt.%, a MgO content of 1.22 wt.%, and a SiO2 content of 1.22 wt.%, and the yield of the selected titanium concentrate is 92.02%; (2) The selected titanium concentrate is smelted in an electric furnace to obtain a molten high-titanium slag containing 80.22 wt.% of TiO2, 1.43 wt.% of CaO, 2.46 wt.% of MgO and 2.42 wt.% of SiO2, and 10 wt.% of sodium chloride, which accounts for 10 wt.% of the mass of the molten high-titanium slag, is added to the molten high-titanium slag (the temperature of the molten slag is greater than 1600° C.), and the mixture is stirred for 5 min and then quenched to obtain quenched titanium slag, and the quenched titanium slag is oxidatively roasted in a rotary kiln at a roasting temperature of 1000° C. for 10 min in an air atmosphere (part of the air can be added by utilizing the heat of the electric furnace flue gas) to obtain roasted titanium slag; (3) The transformed roasted titanium slag is subjected to a one-stage hydrochloric acid leaching process to remove impurities. The hydrochloric acid concentration is 15wt.%, the leaching temperature is 150°C, and the leaching time is 2 hours. The obtained titanium-rich material has a TiO2 content of 87.36wt.%, a CaO content of 0.19wt.%, a MgO content of 0.95wt.%, and a SiO2 content of 2.47wt.%, which meets the boiling chlorination requirements. The titanium recovery rate is 99.24%.

[0020] Example 3 (1) A titanium concentrate having a TiO2 content of 44.88 wt.%, a CaO content of 2.56 wt.%, a MgO content of 1.72 wt.%, and a SiO2 content of 3.59 wt.% is ball-milled to -200 mesh ≥ 90%, and a primary flotation process is used for pre-impurity removal. During the pre-impurity removal, 1800 g of a collector sodium oleate and 600 g of an inhibitor sodium hexametaphosphate are added per ton of the titanium concentrate, and the pH value is adjusted to 3.5 with sulfuric acid to obtain a selected titanium concentrate having a TiO2 content of 46.85 wt.%, a CaO content of 0.68 wt.%, a MgO content of 1.03 wt.%, and a SiO2 content of 1.15 wt.%, and the yield of the selected titanium concentrate is 94.65%; (2) The selected titanium concentrate is smelted in an electric furnace to obtain a molten high-titanium slag containing 80.12 wt.% of TiO2, 1.36 wt.% of CaO, 2.13 wt.% of MgO, and 2.32 wt.% of SiO2; 0.5 wt.% of sodium chloride, which accounts for the mass of the molten high-titanium slag, is added to the molten high-titanium slag (the temperature of the molten slag is greater than 1600° C.), and the mixture is stirred for 5 minutes, followed by quenching to obtain quenched titanium slag; and a rotary kiln is used to oxidatively roast the quenched titanium slag. The roasting temperature of the rotary kiln is 950° C., the roasting time is 20 minutes, and the roasting atmosphere is air (part of the air can be added by utilizing the heat of the electric furnace flue gas) to obtain roasted titanium slag; (3) The transformed roasted titanium slag is subjected to a one-stage hydrochloric acid leaching process to remove impurities. The hydrochloric acid concentration is 15wt.%, the leaching temperature is 145°C, and the leaching time is 2 hours. The obtained titanium-rich material has a TiO2 content of 86.98wt.%, a CaO content of 0.21wt.%, a MgO content of 0.97wt.%, and a SiO2 content of 2.39wt.%, which meets the boiling chlorination requirements. The titanium recovery rate is 98.85%.

[0022] Comparative Example 1 did not undergo the pre-impurity removal treatment of Example 1, and the rest was the same as Example 1 (1) ball-milling a titanium concentrate having a TiO content of 45.21 wt.%, a CaO content of 2.75 wt.%, a MgO content of 1.70 wt.%, and a SiO content of 3.56 wt.% to a particle size of -200 mesh ≥ 90%; (2) Smelting titanium concentrate in an electric furnace to obtain molten high-titanium slag containing 75.13 wt.% of TiO2, 2.41 wt.% of CaO, 2.97 wt.% of MgO, and 6.92 wt.% of SiO2; adding 5 wt.% of sodium chloride to the molten high-titanium slag (the temperature of the molten slag is greater than 1600° C.), stirring for 5 minutes, and then quenching to obtain quenched titanium slag; oxidative roasting the quenched titanium slag in a rotary kiln, the rotary kiln roasting temperature is 900° C., the roasting time is 30 minutes, and the roasting atmosphere is air to obtain roasted titanium slag; (3) The transformed roasted titanium slag was subjected to a one-stage hydrochloric acid leaching process to remove impurities. The hydrochloric acid concentration was 20wt.%, the leaching temperature was 140°C, and the leaching time was 2 hours. The obtained titanium-rich material had a TiO2 content of 81.58wt.%, a CaO content of 0.86wt.%, a MgO content of 1.68wt.%, and a SiO2 content of 5.68wt.%, which could not meet the boiling chlorination requirements. The titanium recovery rate was 93.15%.

[0023] Comparative Example 2: No sodium chloride was added during water quenching, and the other conditions were the same as those of Example 1. (1) A titanium concentrate having a TiO2 content of 45.21 wt.%, a CaO content of 2.75 wt.%, a MgO content of 1.86 wt.%, and a SiO2 content of 3.56 wt.% is ball-milled to -200 mesh ≥ 90%, and pre-impurities are removed by a primary flotation process. During the pre-impurities removal, 2000 g of sodium oleate as a collector and 300 g of water glass as an inhibitor are added per ton of the titanium concentrate, and the pH value is adjusted to 4 with sulfuric acid. The pre-impurities are removed to obtain a selected titanium concentrate having a TiO2 content of 47.15 wt.%, a CaO content of 0.61 wt.%, a MgO content of 0.98 wt.%, and a SiO2 content of 1.12 wt.%, and the yield of the selected titanium concentrate is 94.18%; (2) smelting the selected titanium concentrate in an electric furnace to obtain a molten high-titanium slag containing 80.68 wt.% of TiO2, 1.23 wt.% of CaO, 1.95 wt.% of MgO and 2.42 wt.% of SiO2, and quenching the molten high-titanium slag to obtain quenched titanium slag; oxidatively roasting the quenched titanium slag in a rotary kiln at a roasting temperature of 900° C. for 30 min in an air atmosphere to obtain roasted titanium slag; (3) The transformed roasted titanium slag is subjected to a one-stage hydrochloric acid leaching process to remove impurities. The hydrochloric acid concentration is 20wt.%, the leaching temperature is 140°C, and the leaching time is 2 hours. The obtained titanium-rich material has a TiO2 content of 84.56wt.%, a CaO content of 0.36wt.%, a MgO content of 1.28wt.%, and a SiO2 content of 2.36wt.%, which does not meet the boiling chlorination requirements. The titanium recovery rate is 97.12wt.%.

[0024] Comparative Example 3 was not water quenched, and was cooled naturally after adding sodium chloride. Others were the same as in Example 1. (1) A titanium concentrate having a TiO2 content of 45.21 wt.%, a CaO content of 2.75 wt.%, a MgO content of 1.86 wt.%, and a SiO2 content of 3.56 wt.% is ball-milled to -200 mesh ≥ 90%, and pre-impurities are removed by a primary flotation process. During the pre-impurities removal, 2000 g of sodium oleate as a collector and 300 g of water glass as an inhibitor are added per ton of the titanium concentrate, and the pH value is adjusted to 4 with sulfuric acid. The pre-impurities are removed to obtain a selected titanium concentrate having a TiO2 content of 47.15 wt.%, a CaO content of 0.61 wt.%, a MgO content of 0.98 wt.%, and a SiO2 content of 1.12 wt.%, and the yield of the selected titanium concentrate is 94.18%; (2) The selected titanium concentrate is smelted in an electric furnace to obtain a molten high-titanium slag containing 80.68 wt.% of TiO2, 1.23 wt.% of CaO, 1.95 wt.% of MgO and 2.42 wt.% of SiO2, and sodium chloride accounting for 5 wt.% of the mass of the molten high-titanium slag is added to the molten high-titanium slag (the temperature of the molten slag is greater than 1600° C.) and stirred for 5 minutes. The mixture is naturally cooled and crushed to -1 mm to obtain titanium slag with added sodium chloride; the titanium slag with added sodium chloride is oxidatively roasted in a rotary kiln at a roasting temperature of 900° C. for 30 minutes in an air atmosphere to obtain roasted titanium slag; (3) The transformed roasted titanium slag is subjected to a one-stage hydrochloric acid leaching process to remove impurities. The hydrochloric acid concentration is 20wt.%, the leaching temperature is 140°C, and the leaching time is 2 hours. The obtained titanium-rich material has a TiO2 content of 82.12wt.%, a CaO content of 0.39wt.%, a MgO content of 1.22wt.%, and a SiO2 content of 2.39wt.%, which does not meet the boiling chlorination requirements. The titanium recovery rate is 95.56wt.%.

[0025] Comparative Example 4 does not carry out rotary kiln oxidation roasting, and the rest is the same as Example 1 (1) A titanium concentrate having a TiO2 content of 45.21 wt.%, a CaO content of 2.75 wt.%, a MgO content of 1.86 wt.%, and a SiO2 content of 3.56 wt.% is ball-milled to -200 mesh ≥ 90%, and pre-impurities are removed by a primary flotation process. During the pre-impurities removal, 2000 g of sodium oleate as a collector and 300 g of water glass as an inhibitor are added per ton of the titanium concentrate, and the pH value is adjusted to 4 with sulfuric acid. The pre-impurities are removed to obtain a selected titanium concentrate having a TiO2 content of 47.15 wt.%, a CaO content of 0.61 wt.%, a MgO content of 0.98 wt.%, and a SiO2 content of 1.12 wt.%, and the yield of the selected titanium concentrate is 94.18%; (2) The selected titanium concentrate is smelted in an electric furnace to obtain a molten high-titanium slag containing 80.68 wt.% of TiO2, 1.23 wt.% of CaO, 1.95 wt.% of MgO and 2.42 wt.% of SiO2, and 5 wt.% of sodium chloride by mass of the molten high-titanium slag (the temperature of the molten slag is greater than 1600° C.) is added to the molten high-titanium slag, the mixture is stirred for 5 minutes and then quenched to obtain quenched titanium slag; (3) The quenched titanium slag is subjected to a one-stage hydrochloric acid leaching process to remove impurities. The hydrochloric acid concentration is 20wt.%, the leaching temperature is 140°C, and the leaching time is 2 hours. The obtained titanium-rich material has a TiO2 content of 80.68wt.%, a CaO content of 0.32wt.%, a MgO content of 1.11wt.%, and a SiO2 content of 2.41wt.%, which does not meet the boiling chlorination requirements. The titanium recovery rate is 88.56%.

Claims

1. A process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate, characterized by: The specific steps are as follows: (1) beneficiating the titanium concentrate to obtain a concentrated titanium concentrate with CaO < 0.8 wt.%, MgO ≤ 1.5 wt.%, and SiO2 ≤ 1.2 wt.%; (2) Smelting the selected titanium concentrate in an electric furnace to obtain molten high-titanium slag, adding 0.5%-10% of sodium chloride by weight of the molten high-titanium slag to the molten high-titanium slag, stirring, and quenching to obtain quenched titanium slag; oxidatively roasting the quenched titanium slag in a rotary kiln, the rotary kiln roasting temperature is 900-1000° C., the roasting time is 10-30 min, and roasted titanium slag is obtained; (3) The roasted titanium slag is subjected to a hydrochloric acid leaching to remove impurities at a leaching temperature of 140-150° C. for a leaching time of 2 hours to obtain a titanium-rich material for boiling chlorination.

2. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 1, characterized in that In the titanium-rich material used for boiling chlorination in step (3), TiO2≥85wt.%, CaO≤0.2wt.%, MgO≤1.0wt.%, and SiO2≤2.5wt.%.

3. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 1, characterized in that: During mineral processing, the titanium concentrate is first ball-milled, and then sodium oleate and inhibitors are added. The amount of sodium oleate added is 1500-2000g / t, and the inhibitor water glass is 300-800g / t. The pH value is adjusted to 3-4 with inorganic acid, and a single flotation is used for pre-impurity removal to obtain the selected titanium concentrate.

4. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 1, characterized in that After smelting in an electric furnace, when the temperature of the molten high-titanium slag drops to >1600°C, sodium chloride is added and stirred for 5 minutes.

5. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 1, characterized in that The calcining atmosphere is a mixture of air and oxygen or air.

6. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 1, characterized in that The inhibitor is water glass or sodium hexametaphosphate.

7. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 3, characterized in that The inorganic acid is a sulfuric acid solution.

8. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 1, characterized in that The TiO2 content in the molten high-titanium slag is ≥80wt.%.

9. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 1, characterized in that The concentration of the hydrochloric acid is 20 wt.%.

10. The process for preparing titanium-rich material from titanium concentrate with high titanium recovery rate according to claim 3, characterized in that: In the step (1), the raw material titanium concentrate contains TiO2≥44wt.%, and the ball milling fineness of the titanium concentrate is -200 mesh≥90%.

Citation Information

Patent Citations

  • Preparation method of titanium-rich material and preparation method of titanium tetrachloride

    CN113862494A